2005
DOI: 10.1007/s10681-005-9007-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of drought-avoidance root traits in the mini-core germplasm collection of chickpea (Cicer arietinum L.).

Abstract: SummaryExtensive and deep root systems have been recognized as one of the most important traits for improving chickpea (Cicer arietinum L.) productivity under progressively receding soil moisture conditions. However, available information on the range of variation for root traits is still limited. Genetic variability for the root traits was investigated using a cylinder culture system during two consecutive growth seasons in the mini-core germplasm collection of ICRISAT plus several wild relatives of chickpea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
216
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 241 publications
(245 citation statements)
references
References 16 publications
12
216
1
Order By: Relevance
“…This genotype showed the highest CGR among the entries (3.13 g m -2 day -1 ), and fairly low WUE till early reproductive stage indicated by the second highest Δ 13 C as 20.4‰. In a previous report, ICC 7571 had been shown to possess a larger root biomass ranking the top 16 th among the chickpea mini-core germplasm collection which comprise 216 diverse chickpea genotypes (Kashiwagi et al, 2005).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This genotype showed the highest CGR among the entries (3.13 g m -2 day -1 ), and fairly low WUE till early reproductive stage indicated by the second highest Δ 13 C as 20.4‰. In a previous report, ICC 7571 had been shown to possess a larger root biomass ranking the top 16 th among the chickpea mini-core germplasm collection which comprise 216 diverse chickpea genotypes (Kashiwagi et al, 2005).…”
Section: Discussionmentioning
confidence: 74%
“…Compared to most other legumes, root system of chickpea is known to be well adapted for growing under receding soil moisture conditions by possessing more number of thin xylem vessels facilitating effective, less energy-requiring soil moisture absorption (Purushothaman et al, 2013). Also in chickpea, a large genetic diversity has been reported on the root biomass as well as rooting depth, and promising genotypes were also identified (Kashiwagi et al, 2005). Though the heritability of the rooting depth was not high enough meriting consideration for breeding, the root biomass and root length density does merit (Kashiwagi et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A minicore collection (n=211) of chickpea germplasms was developed at ICRISAT (Upadhyaya and Ortiz, 2001), and it was evaluated for root traits using the cylinder culture system subsequently. Large and significant variation was found among the accessions of the minicore collection for root length density (RLD), root dry weight (RDW), rooting depth (RDp) and root to total plant weight ratio (R/T) (Kashiwagi et al, 2005). The signifi cant genotype × season interaction that occurred for RLD and R/T in this study was found to be of noncrossover type.…”
Section: Current Research Status On Drought Avoidance Root Traits In mentioning
confidence: 57%
“…Kashiwagi et al (2006Kashiwagi et al ( , 2005 and Reynolds and Tuberosa (2008) in chickpeas viewed that deep and prolific root system contributes directly to productivity under water limited conditions. Number of primary branches per plant increased only in 200 Gy (15.9228) while in all other treatments it decreases compare to control (14.3166) and 0.04% HZ (7.2083) inhibited maximum.…”
Section: Resultsmentioning
confidence: 99%